Perancangan Poster Ergonomis untuk Anak Usia Dini di POS PAUD Melati Putih, Kota Bandung - Ica Ramawisari; Nurul Fitriana Bahri; Teuku Zulkarnain Muttaqien (LPPM STIKI Malang, 2024)
Early childhood is susceptible to physical disorders due to incorrect sitting posture and lack of understanding of safety during earthquakes, especially in the city of Bandung which is located near the Lembang Fault. The study aimed to design a poster that was ergonomic and easy for early children to understand, focusing on correct sitting posture and safety measures during an earthquake. This research uses a mixed-methods approach with a descriptive analysis framework. The poster design process involves the needs analysis stage, design concept making, and trials in early childhood at the POS PAUD Melati Putih, Bandung City. Data was collected through direct observation, interviews with teachers and parents, and poster trials to children to evaluate their understanding and response to poster design. The results of the study resulted in two posters: one about ergonomic sitting posture and one about safety measures during an earthquake. The posters are designed using attractive illustrations and bright colors to make it easier for children to understand. Based on the results of observations and interviews with teachers, it can be identified that children are easier to understand and remember the information conveyed through the poster. Ergonomic posters help prevent physical complaints due to incorrect sitting posture, while safety posters increase children's awareness and preparedness for earthquakes.